2022
DOI: 10.3390/diagnostics12020256
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Radiomics Nomogram Integrating Three-Dimensional Features Based on Carotid Plaques to Evaluate Coronary Artery Disease

Abstract: This study aimed to explore the feasibility of ultrasound radiomics analysis before invasive coronary angiography (ICA) for evaluating the severity of coronary artery disease (CAD) quantified by the SYNTAX score (SS). This study included 105 carotid plaques from 105 patients (64 low-SS patients, 41 intermediate-high-SS patients). The clinical characteristics and three-dimensional ultrasound (3D-US) features before ICA were assessed. Ultrasound images of carotid plaques were used for radiomics analysis. Least a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Internal validation was performed in 14 studies ( 25 - 27 , 29 , 32 - 38 , 40 , 41 , 43 ), and 1 study employed external validation ( 42 ), but only 12 studies ( 25 , 26 , 29 , 32 - 34 , 36 - 38 , 40 , 41 , 43 ) reported the AUCs of the validation groups, ranging from 0.73 to 0.986. Model calibration was investigated in 7 studies (36.8%) and demonstrated good calibration performance ( 25 , 30 , 32 , 37 , 40 , 42 , 43 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Internal validation was performed in 14 studies ( 25 - 27 , 29 , 32 - 38 , 40 , 41 , 43 ), and 1 study employed external validation ( 42 ), but only 12 studies ( 25 , 26 , 29 , 32 - 34 , 36 - 38 , 40 , 41 , 43 ) reported the AUCs of the validation groups, ranging from 0.73 to 0.986. Model calibration was investigated in 7 studies (36.8%) and demonstrated good calibration performance ( 25 , 30 , 32 , 37 , 40 , 42 , 43 ).…”
Section: Resultsmentioning
confidence: 99%
“…Only 1 study described the full prediction model ( 36 ), and 8 studies used a nomogram to explain how the models generated personalized predictions (item 15b). Finally, 2 studies failed to discuss the implications for further research ( 33 , 36 ), and appendix information was not available in 7 studies ( 26 , 27 , 30 , 31 , 35 , 37 , 39 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 20 A higher SS suggests more severe atherosclerosis in the coronary arteries, which can adversely affect the patient's life and quality, indicating a poor prognosis and an increased risk of future cardiovascular events, potentially leading to life-threatening conditions. 21 Percutaneous coronary intervention (PCI) is tailored based on the SS level, highlighting the importance of accurate assessment. The ability to noninvasively identify such patients is especially valuable, considering the limitations of ICA, and plays a significant role in both clinical evaluation and enhancing patient outcomes.…”
Section: Discussionmentioning
confidence: 99%